CD8+ and CD4+ T lymphocyte responses against malaria - Kuk, Salih (Ankara Microbiology Soc, 2007)
Malaria which is caused by protozoa of Plasmodium genus, is still a major health care problem especially in tropical and subtropical regions. The global burden of malaria is enormous and continues to grow. This has been attributed to the emergence of drug resistant Plasmodium strains, insecticide resistant Anopheles mosquito vectors, climatic and environmental changes, medico-social and economical malfunctions, presence of co-infections and the lack of an effective and safe malaria vaccine. Host response against malaria is multifactorial, including complicated mechanisms of humoral and cell-mediated immunity. CD8(+) T lymphocytes play a key role in protection against pre-erythrocytic stages of malaria. Hence, many vaccine strategies are focused on QD8(+) T cell response. The development and maintenance of memory CD8(+) T cell response are closely related to the CD4(+) T cells together with interleukin (IL)-4, IL-7, IL-15 and IL-2. CD4(+) T cells also play a triple role in the immune response to malaria parasites; by activating B cells to Produce high level of antimalarial antibodies, by enhancing the induction of CD8(+) T cell responses, and by inhibiting the development of liver stage parasites. Although it has been known much about CD8(+) T and CD4(+) T cell responses, cross-talking mechanisms of these cells, and other factors which contribute to this response during malaria so far, many questions also need to be answered in the future. In this review article, CD8(+) T and CD4(+) T cell responses to malaria infection have been discussed in the light of current literature.
S?tmaya karş? CD8+ ve CD4+ T lenfosit yan?t?
Keywords: malaria; Plasmodium; immune response; CD8(+) T lymphocyte; CD4(+) T lymphocyte